The Impact of Biofilm Formation on the Persistence of Candidemia - Li, Wei-Sin; Chen, Yi-Chun; Kuo, Shu-Fang; Chen, Fang-Ju; Lee, Chen-Hsiang (Frontiers in Microbiology, 2018)
This study aimed to determine the predictors of persistent candidemia and examine the impact of biofilm formation by Candida isolates in adult patients with candidemia. Of the adult patients with candidemia in Kaohsiung Chang Gung Memorial Hospital between January 2007 and December 2012, 68 case patients with persistent candidemia (repeated candidemia after a 3-day systemic antifungal therapy) and 68 control patients with non-persistent candidemia (Candida clearance from the bloodstream after a 3-day systemic antifungal therapy) were included based on propensity score matching and matching for the Candida species isolated. Biofilm formation by the Candida species was assessed in-vitro using standard biomass assays. Presence of central venous catheters at diagnosis (adjusted odd ratio [AOR], 3.77; 95% confidence interval [CI], 1.09–13.00, p = 0.04), infection with higher biofilm forming strains of Candida species (AOR, 8.03; 95% CI, 2.50–25.81; p < 0.01), and receipt of suboptimal fluconazole doses as initial therapy (AOR, 5.54; 95% CI, 1.53–20.10; p < 0.01) were independently associated with persistent candidemia. Biofilm formation by Candida albicans, C. tropicalis, and C. glabrata strains was significantly higher in the case patients than in the controls. There were no significant differences in the overall mortality and duration of hospitalization between the two groups. Our data suggest that, other than presence of retained central venous catheters and use of suboptimal doses of fluconazole, biofilm formation was highly associated with development of persistent candidemia.